The Southern Ocean diatom Pseudo-nitzschia subcurvata flourished better under simulated glacial than interglacial ocean conditions: Combined effects of CO2 and iron. - Anna Pagnone; Florian Koch; Franziska Pausch; Scarlett Trimborn (PLoS ONE)
The 'Iron Hypothesis' suggests a fertilization of the Southern Ocean by increased dust deposition in glacial times. This promoted high primary productivity and contributed to lower atmospheric pCO2. In this study, the diatom Pseudo-nitzschia subcurvata, known to form prominent blooms in the Southern Ocean, was grown under simulated glacial and interglacial climatic conditions to understand how iron (Fe) availability (no Fe or Fe addition) in conjunction with different pCO2 levels (190 and 290 μatm) influences growth, particulate organic carbon (POC) production and photophysiology. Under both glacial and interglacial conditions, the diatom grew with similar rates. In comparison, glacial conditions (190 μatm pCO2 and Fe input) favored POC production by P. subcurvata while under interglacial conditions (290 μatm pCO2 and Fe deficiency) POC production was reduced, indicating a negative effect caused by higher pCO2 and low Fe availability. Under interglacial conditions, the diatom had, however, thicker silica shells. Overall, our results show that the combination of higher Fe availability with low pCO2, present during the glacial ocean, was beneficial for the diatom P. subcurvata, thus contributing more to primary production during glacial compared to interglacial times. Under the interglacial ocean conditions, on the other hand, the diatom could have contributed to higher carbon export due to its higher degree of silicification.